Propuesta de mejoramiento de la productividad enfocado en la metodología six sigma en la ladrillera De Lago. - Achanga Campoverde, Wagner Adrian (2021)
The project "PROPOSAL TO IMPROVE PRODUCTIVITY FOCUSED ON THE SIX SIGMA METHODOLOGY AT LA BRILLERA DE LAGO" aimed to present in most companies to improve their processes, and this, in turn, enhances the product that is offered. One of the tools that offer a type of improvement in company processes is the SIX SIGMA methodology, which identifies failures in production processes and analyzes them to improve procedures. This methodology is somewhat ambitious in its results, seeking to obtain quality in the product up to high perfection levels, proposing at its highest level a figure of 3.4 errors per million opportunities. The idea of using the SIX SIGMA tool will allow the company's workers to obtain knowledge in the management of the processes. They are guided by the proposals for continuous improvements and carrying out an estimation or assessment of the capacities they propose to acquire, hoping to obtain increased production and product quality.